Operational Modal Analysis of Wind Turbine Speed-increase Gearbox - LI Yafeng; XU Yuxiu (Institute of Advanced Engineering and Science, 2013)
Speed increase transmission gear box is the primary vibration and noise source of wind turbine, Operational modal method was adopted to collect impact data and response data of each point based on the gearbox test model. ANSYS finite element model is established to simulate the wind turbine gearbox. Then the modal frequencies of the two methods were compared to ensure the test model is correct. The results show that operational modal method can be applied in wind turbine gearbox modal analysis and it has important guiding significance to gearbox fault diagnosis and reliability and maintainability improving. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3518